Kajian Hidrologi pada Satuan Penggunaan Lahan Kawasan Pegunungan Kapur Karangbolong Jawa Tengah - Sutarno Sutarno (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2012)
Tittle : Study of Hidrology on Landuse Units Topography Karst Karangbolong. The objective of the research is to study of hidrology on landuse units topography karst Karangbolong. The methods of the research was descriptive analysis and  field survey on land units from maps overlays i.e geohidrology map, soilmap, geology map and landuse of Karangbolong map. The result of the research is that Karangbolong western hilly area and its surrounding  which an area 234 km2.  The  research area  has a high potential of water resources, due to several reason  the water cannot be used by people for agriculture purposes. The landuse forest is mainly belonging to Perhutani. On the stony area Tmk and Tmph or on U1,U2,U3 landuse units area or P1,P2,P3,  landuse located on the middle and northern does not change  too much and hydrological function is relative unchanged, but the southern area the landuse change too much. Therefore several activities experiences disturbance such as drying water resources and the formation of stalactite and stalagmite, and also several change of landuse such as paddy field becoming arid land, forest becoming settlement area and arid land.